Rewarming From Hypothermic Cardiac Arrest Applying Extracorporeal Life Support: A Systematic Review and Meta-Analysis - Bjertnæs, Lars J.; Hindberg, Kristian; Næsheim, Torvind O.; Suborov, Evgeny V.; Reierth, Eirik; Kirov, Mikhail Y.; Lebedinskii, Konstantin M.; Tveita, Torkjel (Frontiers in Medicine, 2021)
Introduction: This systematic review and meta-analysis aims at comparing outcomes of rewarming after accidental hypothermic cardiac arrest (HCA) with cardiopulmonary bypass (CPB) or/and extracorporeal membrane oxygenation (ECMO). Material and Methods: Literature searches were limited to references with an abstract in English, French or German. Additionally, we searched reference lists of included papers. Primary outcome was survival to hospital discharge. We assessed neurological outcome, differences in relative risks (RR) of surviving, as related to the applied rewarming technique, sex, asphyxia, and witnessed or unwitnessed HCA. We calculated hypothermia outcome prediction probability score after extracorporeal life support (HOPE) in patients in whom we found individual data. P< 0.05 considered significant. Results: Twenty-three case observation studies comprising 464 patients were included in a meta-analysis comparing outcomes of rewarming with CPB or/and ECMO. One-hundred-and-seventy-two patients (37 %) survived to hospital discharge, 76 of 245 (31 %) after CPB and 96 of 219 (44 %) after ECMO; 87 % and 75 %, respectively, had good neurological outcomes. Overall chance of surviving was 41 % higher (P=0.005) with ECMO as compared with CPB. A man and a woman had 46 % (P=0.043) and 31 % (P=0.115) higher chance, respectively, of surviving with ECMO as compared with CPB. Avalanche victims had the lowest chance of surviving, followed by drowning and people losing consciousness in cold environments. Assessed by logistic regression, asphyxia, unwitnessed HCA, male sex, high initial body temperature, low pH and high serum potassium (s-K+) levels were associated with reduced chance of surviving. In patients displaying individual data, overall mean predictive surviving probability (HOPE score; n=134) was 33.9 % ± 33.6 % with no significant difference between ECMO and CPB-treated patients. We also surveyed 80 case reports with 96 victims of HCA, who underwent resuscitation with CPB or ECMO, without including them in the meta-analysis. Conclusions: The chance of surviving was significantly higher after rewarming with ECMO, as compared to CPB, and in patients with witnessed compared to unwitnessed HCA. Avalanche victims had the lowest probability of surviving. Male sex, high initial body temperature, low pH and high s-K+ were factors associated with low surviving chances.